2002
DOI: 10.1093/milmed/167.6.464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spouse Abuse Treatment: Description and Evaluation of the Air Force Family Advocacy Programs for Spouse Physical Abuse

Abstract: Data are reported from a sample of 2,991 spouse physical abusers who received Air Force Family Advocacy Program (FAP) services and who volunteered to complete program evaluation measures that were administered before and after treatment and at a 6-month follow-up. As expected, after treatment compared with before treatment, professionals rated offenders as less at risk, and the offenders indicated general satisfaction with the Family Advocacy Program services. Additionally, as predicted, objective measures ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
1
8
1
1
Order By: Relevance
“…This study found that a quarter of Army soldier spouse abuse offenders were using substances, primarily alcohol, at the time of the spouse abuse incident. This estimate of the extent and type of substance use during abusive incidents is similar to that found in other research with active-duty military populations (Brewster et al, 2002;Chapin & Brannen, 2002;McCarroll et al, 1999). The predominant use of alcohol, rather than illicit drugs, may be because of the routine testing for illicit drugs that occurs in the Army, and the fact that illicit drug use could result in being discharged from the Army (Department of the Army, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study found that a quarter of Army soldier spouse abuse offenders were using substances, primarily alcohol, at the time of the spouse abuse incident. This estimate of the extent and type of substance use during abusive incidents is similar to that found in other research with active-duty military populations (Brewster et al, 2002;Chapin & Brannen, 2002;McCarroll et al, 1999). The predominant use of alcohol, rather than illicit drugs, may be because of the routine testing for illicit drugs that occurs in the Army, and the fact that illicit drug use could result in being discharged from the Army (Department of the Army, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…A study of Army soldiers in a batterer treatment program found that they were significantly more likely than other soldiers to evidence problem drinking behaviors (Hurlbert, Whittaker, & Munoz, 1991). Research with active-duty Navy trainees found that, among both males and females, alcohol problems were positively associated with the perpetration of intimate partner physical violence (Merrill, Hervig, & Milner, 1996), and research with Air Force servicemen and servicewomen found that those with a history of alcohol problems perpetrated more severe intimate partner violence than those without a history of such problems (Brewster, Milner, Mollerstrom, Saha, & Harris, 2002;Rosen, Parmley et al, 2002b).…”
mentioning
confidence: 99%
“…Gang violence in Detroit was found to be overrepresented by young men for example (Wilson and Daly 1985 ). By contrast, in most cases of domestic violence, men act as the perpetrators and women are the victims (Zlotnick et al 1998 ; Brewster et al 2002 ; Miller 2005 ). This is evident from studies in the USA, where only 16% of domestic violence disputes were perpetrated by women (Miller 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The military also provides services for a large number of women identified as committing physical abuse against a spouse. One study of 2,991 Air Force personnel who committed physical abuse against a spouse found that 23% of the offenders were female (Brewster, Milner, Mollerstrom, Saha, & Harris, 2002). Another study of reports of spouse abuse in the Army Central Registry from 1989 to 1997 found that 33% of persons identified as domestic violence offenders were women (McCarroll et al, 1999).…”
mentioning
confidence: 99%